The Significance of the Right Dorsolateral Prefrontal Cortex for Pitch Memory in Non-musicians Depends on Baseline Pitch Memory Abilities - Schaal, Nora K.; Kretschmer, Marina; Keitel, Ariane; Krause, Vanessa; Pfeifer, Jasmin; Pollok, Bettina (Frontiers in Neuroscience, 2017)
Pitch memory is a resource which is shared by music and language. Neuroimaging studies have shown that the right dorsolateral prefrontal cortex (DLPFC) is activated during pitch memory processes. The present study investigated the causal significance of this brain area for pitch memory in non-musicians by applying cathodal and sham transcranial direct current stimulation (tDCS) over the right DLPFC and examining the impact on offline pitch and visual memory span performances. On the overall sample (N= 22) no significant modulation effect of cathodal stimulation on the pitch span task was found. However, when dividing the sample by means of a median split of pre-test pitch memory abilities into a high and low performing group, a selective effect of significantly impaired pitch memory after cathodal tDCS in good performers was revealed. The visual control task was not affected by the stimulation in either group. The results support previous neuroimaging studies that the right DLPFC is involved in pitch memory processes in non-musicians and highlights the importance of baseline pitch memory abilities for the modulatory effect of tDCS.